Features of the structure of the alveolar process in patients with gnatic form of mesial occlusion - A. B. Mallaeva; N. S. Drobysheva (Эндодонтия Today)
Aim. To assess the size of the alveolar ridge / part of the jaws in patients with gnathic mesial occlusion of the dentition.Materials and methods. A study was carried out, during which we determined the structural features of the alveolar ridge of the upper and lower jaws of 50 adult patients (from 18 to 44 years old), and also studied the presence / absence of the relationship of this parameter with the inclination of the teeth.Results. The smallest thickness of the alveolar bone in the upper jaw was observed in the area of the mesio-buccal root of the first molars and in the area of the first premolars and canines. The smallest thickness of the alveolar bone in the lower jaw was observed in the area of the vestibular surface of the first and second premolars, canines and incisors. The greatest thickness of the alveolar bone is observed in the distal-buccal region of the second molars.Conclusions. A natural mechanism promotes dentoalveolar compensation, while maintaining the amount of bone in the region of the vestibular and lingual alveolar bones to maintain the integrity of the periodontium.